"She was very sorry to leave her dresses because she would soon die": a case of suicide in São João do Triunfo-PR County (1928) (Revista de História Regional, 2022)
In the middle of 1928, a housewife had to head to the São João do Triunfo's city center, in the countryside of Paraná, to give her version of her daughter's suicide. In this paper, we analyze the police investigation that involved this particular case. From the witnesses' narrative and the pieces found in the document, such as the corpus delicti exam, we come across themes that involve gender relations, quotidian life, and the crystallization of versions about suicide. When we select a document, among so many, and read it carefully, we dive into a wealth of details and situations. We intend to explore it here. For such a proposal, we rely on Michel Foucault's way of operating and, especially, on part of Brazilian historiography and the History of Violence that help analyze rural areas.